Discovery of sound in the sea: Resources for decision makers - Vigness-Raposa, K.; Scowcroft, G.; Morin, H.; Knowlton, C.; Miller, J.; Ketten, Darlene; Popper, A. (2016)
© 2016 Acoustical Society of America. Research on underwater sound is critical for understanding potential acoustic impacts to marine life. However, such research can be challenging, requiring complex, multidisciplinary approaches. Research results often reach the public through popular media, but these sources sometimes contain misinformation or oversimplify results. To provide a scientifically accurate resource on underwater sound but understandable for a variety of audiences, the University of Rhode Island Graduate School of Oceanography has teamed with Marine Acoustic, Inc. on the Discovery of Sound in the Sea (DOSITS) project. The project's foundation is a website (www.dosits.org) that is a comprehensive, universally available resource that synthesizes the latest peer-reviewed science on underwater sound, updated semiannually with newly published scientific information after a thorough review by a panel of scientific experts. A current focus of the DOSITS project is resources for the international decision making community. Recently, two needs assessment surveys were conducted to identify format and content priorities of government employees, federal and state contractors, nongovernmental organization employees, and industry representatives. Guided by their input, structured tutorials, webinars, and instructional videos were developed to address needs such as science of sound fundamentals, hearing sensitivities, and potential effects of underwater sound on marine animals.